The Factors Affecting Regional Financial Accountability: Organizational Commitment as Moderating Variables (Study on Rokan Hilir District Government OPD) - Febri Yulisa; Vince Ratnawati; Taufeni Taufik (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aims to investigated the effect of government internal control systems, regional financial management information systems and human resource competencies on regional financial accountability. The population in this study were all employees of the regional apparatus of Rokan Hilir Regency. In this study, the sample taken was the Head of regional device organization, Head of regional device organization Financial Subdivision, Treasurer of regional device organization and Accounting Personnel with consideration directly related to financial management and directly involved technically with regional financial accountability. The statistical method used to test the research hypothesis is Structural Equation Model (SEM) based on Partial Least Square (PLS) with the help of WarpPLS 5.0 program. The results of this study indicate that government internal control systems, regional management information systems and human resource competencies affect regional financial accountability. Organizational commitment influences the regional financial management information system towards regional financial accountability, but organizational commitment does not affect the government's internal control system and human resource competence towards regional financial accountability.